L’industrie lithique magdalénienne du gisement de plein-air de la Corne-de-Rollay (Couleuvre, Allier) : entre respect des normes et variabilité des chaînes opératoires - Raphaël Angevin (Revue Archéologique du Centre de la France)
La Corne-de-Rollay (Couleuvre, Allier) is a vast open-air camp-site located on the top of a small plateau, between Cher valley and Allier valley. Here are presented the results of a study of the lithic industry from the Magdalenian occupation of this settlement. Composed of two large groups of raw materials (flint and local siliceous rocks), this industry shows several operative schemes to produce blades and bladelets. The high variability of different bladelets production techniques leads us to question the autonomy of different production systems which are destined to produce blanks with similar morpho-technical characteristics and with the same or complementary morpho-functional features. This consideration invites us to reconsider the phenomenon of the "production lines ramification" (Bourguignon et al. 2004), with different operative schemes able to meet similar production objectives, but established at distinct time scales. Finally, the chrono-cultural attribution of this industry is discussed.